Formulation of Chicken Nuggets with the Addition of Chicken Liver as a Product Rich in Iron and Vitamin A for Adolescent Females - Wibisono, Himawan Haryo; Aries, Muhammad; Nasution, Zuraidah (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The purpose of this study was to develop chicken nuggets with the addition of chicken liver and analyze their nutritional content. Nugget with 10% chicken substituted with chicken liver was the selected formulation. The nutrient profile of the selected nugget formula was: 56.8 g/100 g moisture, 1.46 g/100 g ash, 14.66 g/100 g protein, 6.5 g/100 g fat, 12.92 g/100 g carbohydrates, 16.39 mg/100 g iron, and 760.16 RE /100 g vitamin A. One serving of the selected nugget formula is equivalent to 100 g (4 pieces) that contribute 168 kcal energy. The selected formulations have met the claims for low fat, high in iron and vitamin A, and source of protein.